Butyricimonas faecalis sp. nov., isolated from human faeces and emended description of the genus Butyricimonas. Issue 3 (1st February 2019) - Le Roy, Tiphaine; Van der Smissen, Patrick; Paquot, Adrien; Delzenne, Nathalie; Muccioli, Giulio G.; Collet, Jean-François; Cani, Patrice D.
Abstract : A Gram-negative, strictly anaerobic, non-spore forming, non-motile, non-pigmented bacterial strain, designated H184 T, was isolated from human faeces. 16S rRNA gene sequence analysis showed that strain H184 T represents a member of the genus Butyricimonas . Strain H184 T is related to but distinct from Butyricimonas virosa JCM 15149 T and Butyricimonas paravirosa JCM 18677 T, with 16S rRNA gene sequence similarities of 96.32 and 96.24 %, respectively. Strain H184 T shared 90.50 % hsp60 gene sequence similarity to B. virosa JCM 15149 T and B. paravirosa JCM 18677 T . Growth occurs between 25 and 42 °C with an optimum at 37 °C. Bile and NaCl concentration range allowing growth are 0–3.75 % and 0–1.8 %, respectively. pH range for growth is 5.5–8. The strain produced propionate as the major end product from glucose. The major cellular fatty acids of strain H184 T were iso-C15 : 0 (63.5 %) and iso-C17 : 0 3-OH (12.8%). The major menaquinone of the strain was MK-10 (86 %). DNA G+C content of the isolate H184 T was 44.2 mol%. The genome-based comparison between strain H184 T and B. virosa JCM 15149 T by pairwise average nucleotide identity indicated a clear distinction with a score of 87.22. On the basis of these data, strain H184 T represents a novel species of the genus Butyricimonas, for which the name Butyricimonas faecalis sp. nov. is proposed. The type strain of B. faecalis is H184 T (DSM 106867 T, LMG 30602 T ).